2014
DOI: 10.3109/03014460.2014.909884
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different behavioural factors and obesity status on systolic blood pressure among pre-school children

Abstract: The data showed that high ST exposure time and low SLT are associated with enhanced blood pressure in children at pre-school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Researchers in one of these studies included sleep in their analysis and found mixed results, depending on the specific outcome, of substituting sedentary behavior with sleep ( 108 ). Findings from 2 studies (1 longitudinal ( 89 ) and 1 cross-sectional ( 118 )), both in children, indicated that the addition of high sleep in combination with low screen time and/or physical activity yielded the most favorable cardiometabolic outcomes. No studies included sleep in adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers in one of these studies included sleep in their analysis and found mixed results, depending on the specific outcome, of substituting sedentary behavior with sleep ( 108 ). Findings from 2 studies (1 longitudinal ( 89 ) and 1 cross-sectional ( 118 )), both in children, indicated that the addition of high sleep in combination with low screen time and/or physical activity yielded the most favorable cardiometabolic outcomes. No studies included sleep in adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In children aged from 3 to 8 years TV viewing and screen time, but not computer use, were positively associated with both SBP and DBP after adjusting for potential confounders [31]. Furthermore, there are also studies supporting the influence of screen time on BP levels indirectly through obesity (Schmidt) and through less sleeping time [3,15].…”
Section: Nutrition Examination Survey (Nhanes) and The Nhanes Nationalmentioning
confidence: 98%
“…A reliable method to estimate screen time has been an area for researcher's interest in several decades. automated time-lapse video observations [35] and accelerometers [18,31,36] alone or in combination with self-report questionnaires [2,4,15,27,28] have been evaluated as potential screen time or sedentary time measures. However, whichever method is utilized we may keep in mind that TV time, computer time and total screentime do not represent total sedentary time that better accessed by accelerometers.…”
Section: Nutrition Examination Survey (Nhanes) and The Nhanes Nationalmentioning
confidence: 99%
See 1 more Smart Citation